PEMIKIRAN FILSAFAT MANUSIA IBNU MISKAWAIH: TELAAH KRITIS ATAS KITAB TAHDZIB ALAKHLAQ - Syamsul Bakri (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2018)
This article aims to describe human philosophical thought of Ibn Miskawaih in the book entitled Tahdzib Alakhlaq which is focused on the conception of human being structure; the relation of human material substance (physic) and immaterial substance (soul); the human life ultimate; and the conception of Insan Kamil. Based on the library studies, by using content analysis approach, this study found the historical fact that Ibnu Miskawaih acknowledged; first, the existence of physical essence made human being bound by space, time, and material determination. While the existence of soul made human being be able to build a relationship with God and to create culture and civilization. Second the existence of a structural and functional relationship between physic as a material substance, and soul as an immaterial substance of a human being, and not human immaterial essential relationship. Third, the human life ultimate is to achieve ideal condition, related to their behavior and special characteristic, i.e. faculty of thought. Fourth, the conception of Insan Kamil which is emphasized to the force and magnificence of the faculty of thought that made human left their instincts, syahwiyah and amarah desire toward sharia law and wisdom of thought so that they would be able to achieve to the highest position in the human nature.